O trabalhador introduzido pela Companhia de Agricultura, Imigração e Colonização ao longo dos anos de 1928-1940 no estado de São Paulo (Revista de História Regional, 2025)
With the end of slavery, labor became increasingly necessary for coffee plantations. To meet this demand, various types of jobs were created to introduce immigrant workers. It is also worth noting that there was also the presence of nationals, however, they were seen as a second option for large landowners. In the early years of the 20th century, we observed the work of several companies or private enterprises whose objective was to recruit workers for the state of São Paulo. Among these, the Agriculture, Immigration and Colonization Company (CAIC) stood out, introducing both immigrants and nationals to the state of São Paulo. The objective of this article is to analyze and understand the work of the Agriculture, Immigration and Colonization Company in the introduction of immigrant and national workers between 1928 and 1940, highlighting aspects of the company, as well as the origin of the immigrants and contracts established between the CAIC and the Agriculture Department of the state of São Paulo.